Early Modern Exemplars: Reading Strategies and the Assertion of Readerly Identity and Authority in the Life-writing of Mary Ward, Dionys Fitzherbert and Elizabeth Isham - Martin Thompson (Sillages Critiques)
The recent expansion within early modern studies of the application of the generic label “life-writing” has led to the recognition of the literary and cultural value of an array of previously undervalued texts, particularly those written by women. The inclusion of texts that previously sat outside the canon has proved them powerful enough to disrupt and complicate understandings of the genre, and beyond this, the very paradigms upon which the study of autobiographical writing was historically predicated.  This article combines close readings with material analysis of three female-authored autobiographical manuscripts to suggest that, contrary to Western, Protestant and masculine assumptions, these pious seventeenth-century women perceived of themselves primarily not only as authors but readers of their own divinely-authored life stories. Focusing primarily on the paratexts attached to life narratives of Mary Ward (1585-1645), Dionys Fitzherbert (c.1580-c.1642) and Elizabeth Isham (1609-1654), it identifies – across the Reformation confessional divide – common semantic and grammatical patterns which demonstrate that these texts advocated and illustrated particular reading strategies that encouraged their audiences too to see their own lives as texts to be read. It argues that Mary Ward’s Ignatian-inspired texts in particular represent a radical reimagining of the exemplary function of women’s lives.